Study of the Alamouti-OFDM system using ZP technique and training symbols in multi path selective fading channel - Hadj Ali Bakir; Fatima Debbat; Fethi Tarik Bendimerad (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
In this paper, we propose a modified Alamouti code matrix and it associated with zero padding orthogonal frequency division multiplexing known as (Alamouti- ZP OFDM). Which zero padding (or zeros samples) are adopted over the OFDM symbols that construct also the encoded symbols of the Alamouti matx. Training symbols are applied for the channel estimation. Furthermore, the ML decoding algorithm  is used to get output bits which the BER can be measured. Using the selective multi path fading as model for wireless channel to evaluate the performance provided by the system proposed. The performance of  the approach proposed is based on BER parameter. For that, the system  is simulated  in two profiles of paths number (3 paths, and 6 paths) have used, which the spread delays of these paths are taken (in millisecond and in microsecond) respectively. Different data stream are simulated and compared. And the BER performance are compared also for ifft lengths 512 and 1024 and the BER results presented for all parameters of (paths number, and spread delays). The simulation  results show that the system  presented performed good even the spread delays of multi path channel are great (microseconds or milliseconds) and even increased  the data simulated from  increasing the parallel of the data streams transmitted in the system study . So, the system could keen their effectiveness against of fading channel and ISI phenomenon.  And finaly, it is shown that increasing IFFT samples in the simulation process the improvements are more enhanced of the approach proposed.